Abdominal Paragangliomas: A Single Center Experience - Ahmet Gökhan SARITAŞ; Mehmet Onur GÜL; Orçun YALAV; Zafer TEKE; İsa Burak GÜNEY (Bezmiâlem Science, 2021)

(untitled)
Objective:Paragangliomas are rare tumors arising from extra-adrenal chromaffin tissue, which are widely distributed near or within the autonomic nervous system in the retroperitoneal sites and in the sympathetic ganglia of various viscera. We present a review of our 18-year institutional experience with resected abdominal paragangliomas.Methods:The data collected from 12 patients who underwent surgery due to abdominal paraganglioma in our clinic between 2002 and 2020 were analyzed retrospectively.Results:There were 12 patients in our study. The median age was 44 years (range: 21-81 years). The patients had one or more of the symptoms of headache (n=2, 16,6%), palpitations, abdominal pain (n=5, 41.6%), sweating (n=2, 16.6%) and hypertension (n=5, 41.6%), which are the classic clinical symptoms. One of the cases (1/12; 8,3%) was detected incidentally. The mass location was in the retroperitoneal region in 10 cases (83.3%) and in the pelvic region in 2 cases (16.6%). Five of the patients applied to our clinic with episodes of paroxysmal hypertension, and vanillylmandelic acid and metanephrine levels were found to be high in the blood and 24-h urinary tests. After a median follow-up period of 60 months, only 1 patient (8.3%) had metastasis and required reoperation 2 years after the first operation. One patient (8.3%) died on postoperative 36th month due to cardiac problems.Conclusion:Abdominal paragangliomas are rare tumors whose optimal management requires the surgeon to be highly attentive to the disease course, from diagnosis of functioning or nonfunctioning lesions, through operative treatment that may require adjacent organ resection, to lifelong follow-up for recurrences.